Theoretical study on monometallic cyanide cluster fullerenes YCN@C72. Issue 6 (22nd December 2015) - Gao, Xu; Zhao, Li‐Juan; Wang, Dong‐Lai
Abstract : The geometries, stabilities, and electronic properties of new endohedral fullerene YCN@C72 have been investigated by the B3LYP and PBE1PBE density functional (DFT) methods. The C2v (11188)‐C72 cage, which violates the isolated pentagon rule (IPR) with a pair of fused pentagons, is predicted to be the lowest energy isomer for both empty C 72 2 ‐ and YCN@C72 . The relatively large HOMO‐LUMO gap (B3LYP: 1.48 eV, PBE1PBE: 1.68 eV) for YCN@C2v (11188)‐C72 reveals this structure kinetic stability. Significantly, the encased YCN cluster adopts a triangular structure inside the C2v (11188)‐C72 cage, similar to the results reported on YCN@Cs (6)‐C82 and TbCN@C2 (5)‐C82 . Furthermore, the vertical ionization potential and electron affinity, UV‐vis‐NIR and IR spectra of YCN@C2v (11188)‐C72 have been predicted to facilitate future experimental characterization. © 2015 Wiley Periodicals, Inc. Abstract : New endohedral YCN@C72 metallofullerenes have been systematically investigated by means of DFT calculations. YCN@C2v (11188)‐C72, which violates the isolated pentagon rule with a pair of fused pentagons, is the most stable structure. The relatively large energy gap and high aromaticity are related to the high chemical stability of this species, in which the encaged YCN molecules employs a triangular structure similar to that characterized in YCN@Cs (6)‐C82 and TbCN@C2 (5)‐C82 .